Effective Use of Blended Learning Flipped Classroom Type Reviewed from Student Learning Outcomes in Digital Simulation Subjects at SMK Negeri 3 Surakarta - Kausar, Alfin; Maryono, Dwi; Aristyagama, Yusfia Hafid (Journal of Informatics and Vocational Education, 2020)
This study aims to find out (1) differences in student learning outcomes in the application of blended learning model flipped classroom type with enriched virtual learning model (2) more effective learning model between blended learning model flipped classroom type and enriched virtual learning model. The research method used is a quantitative quasi-experimental design by using pretest-posttest control. The population in this study is all students of grade X majoring in Accounting and Finance of SMK Negeri 3 Surakarta Institution. The sample used in this study was 72 students. Sampling techniques in this research are by total sampling method. Data obtained from pre-test and post-test results based on indicators of student learning outcomes. The results obtained from this study are as follows. First, there are differences in learning outcomes in Digital Simulation subjects in experimental classes by applying flipped classroom type blended learning models and control classes by applying enriched virtual learning models. Evidence from the average study results of experimental classes of 82.94 and control classes of 75.39. Second, flipped classroom blended learning models are more effective than enriched virtual learning models. The effectiveness of applying flipped classroom type blended learning models in experimental classes is in a moderate category, while the effectiveness of implementing enriched virtual learning models in control classes is in a low category.